SEED GERMINATION AND SEEDLING FORMATION OF Eugenia stictopetala (MYRTACEAE) UNDER DIFFERENT ENVIRONMENTAL CONDITIONS - Fernandes, Richard Matheus; Abreu, Clara Anne Araújo; Oliveira, Ademir Kleber Morbeck (Floresta, 2019)
The species Eugenia stictopetala, known as “cambucá” or dog-tongue, is found in areas of Cerrado and produces fruits in the form of drupe, black when mature and much consumed by the fauna. Despite its potential for use, there is no information about its germination processes and for this reason, the objective of this work was to evaluate its germination and seedling formation at different temperatures, besides its germination after initial storage. Newly collected seeds from the Cerrado area were evaluated at six temperatures (20, 25, 30, 35, 20-30 and 25-35 °C) and after 35 days of storage in different environmental conditions in a completely randomized design. The results indicated that the seeds have a high water content and the temperature of 30 °C being the most suitable for germination and seedling formation. After storage, loss of water content occurs, leading to a reduction in germination rates, indicating a characteristic of recalcitrant seeds.